Bonobo Optimizer Algorithm for Thermomechanical Stability Analysis of Laminated Plates with a Hole - Shaterzadeh, Alireza; Topal, Umut; Hadad, Vahid; Das, Amit Kumar (International journal of steel structures, 2025)
This study focuses on the thermomechanical optimization of buckling resistance in laminated composite plate with a hole. The goal is to maximize the critical buckling load by identifying optimal fiber orientations within the layers using the Bonobo Optimizer Algorithm (BOA). The first-order shear deformation theory (FSDT) is employed to determine elastic buckling loads under combined thermomechanical loading. Numerical investigations are conducted for various parameters, including uniform temperature rises, edge loading conditions, support configurations, hole size ratios, load ratios, and geometric proportions. The results showed that these parameteres play a vital role in the the buckling load optimization of laminate composite plate with a hole. The study shows CCCC and SFSF boundary conditions yield the highest and lowest buckling loads, respectively. Critical buckling load decreases with temperature rise. Plates without cut-outs outperform those with cut-outs, and shorter plates under negative temperature rise achieve maximum buckling load. Uniform loading results in the lowest buckling capacity due to its larger loading area.